2022
DOI: 10.3389/fonc.2022.893132
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Macrophages Correlate With Prognosis in Medulloblastoma

Abstract: PurposeMacrophage polarization plays an essential role in the tumor microenvironment of brain tumors. However, the role of tumor-associated macrophages (TAMs) in medulloblastoma still remains controversial. Thus, we investigated the distribution of macrophages in medulloblastoma tissues and analyzed the association of TAM recruitment and medulloblastoma patients’ outcomes.MethodsWe obtained a total of 71 paraffin sections from patients with medulloblastoma, and detected the activated phenotype (M1/M2) by monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…High in ltration of M1 macrophages signi cantly reduced survival time in prostate cancer patients [26]. The M1 macrophage content was signi cantly higher in the metastatic group than in the non-metastatic group of medulloblastoma [34]. Our results also showed that increased CENPO expression was associated with poor LUAD survival.…”
Section: Discussionsupporting
confidence: 56%
“…High in ltration of M1 macrophages signi cantly reduced survival time in prostate cancer patients [26]. The M1 macrophage content was signi cantly higher in the metastatic group than in the non-metastatic group of medulloblastoma [34]. Our results also showed that increased CENPO expression was associated with poor LUAD survival.…”
Section: Discussionsupporting
confidence: 56%
“…The infiltration of tumor-associated macrophages (TAMs) and increased expression of their associated genes, CD163 and CSF1R, were significantly observed in SHH MBs [ 47 ]. An increase in M1 macrophages was reported to correlate with good outcomes of MB [ 48 ]. Furthermore, macrophage reduction in TME were correlated with poorer outcomes of SHH MBs, and TAMs might be involved in inhibiting tumor growth in SHH MBs [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because TAMs are composed of variable amounts of microglia and macrophages, the composition of TAMs are different in all MB subgroups. Margol et al [ 58 ] and Zhang et al [ 59 ] reported that TAMs were significantly higher in SHH-MB compared to other MB subgroups. This may be due to the high expression of monocyte chemotactic protein-1 (MCP-1], which helps in TAM recruitment and M2 polarization[ 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [ 63 ] suggested that a large number of M1-polarized TAMs was associated with worsening outcome in SHH-MB patients. Lee and his group has also investigated the correlation between TAM recruitment and outcome, and they revealed that expressed M1-polarized TAMs predicted better progression-free survival but, TAMs showed no significant effect on OS[ 59 ]. Few studies showed that the immunoreactivity in MB microenvironment, regardless the subtype, is age-related[ 64 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation